2003
DOI: 10.1046/j.1471-4159.2003.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effects of NGF and IGF‐1 on neurite growth in adult sensory neurons: convergence on the PI 3‐kinase signaling pathway

Abstract: Nerve growth factor (NGF) and insulin-like growth factor-1 (IGF-1) play an important role in promoting axonal growth from dorsal root ganglion (DRG) neurons. Adult DRG neurons exhibit neurotrophin-independent survival, providing an excellent system with which to study trophic factor effects on neurite growth in the absence of significant survival effects. Using young adult rat DRG neurons we have demonstrated a synergistic effect of NGF plus IGF (N + I), compared with either factor alone, in promoting neurite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 56 publications
9
116
1
Order By: Relevance
“…The essential role of the PI3K/AKT signalling pathway in stimulating axon regenerative processes in the adult central and peripheral nervous systems is well documented 8,[27][28][29][30] . Activated AKT phosphorylates GSK3a at serine 21 (pGSK3a) and GSK3b at serine 9 (pGSK3b) and thereby inhibits their respective kinase activity 7,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The essential role of the PI3K/AKT signalling pathway in stimulating axon regenerative processes in the adult central and peripheral nervous systems is well documented 8,[27][28][29][30] . Activated AKT phosphorylates GSK3a at serine 21 (pGSK3a) and GSK3b at serine 9 (pGSK3b) and thereby inhibits their respective kinase activity 7,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I may also have an anti-apoptotic effect, as the phosphorylation of forkhead proteins, important mediators of growth factorstimulated cellular survival, also depends upon PI 3-K and Akt [35]. It is clear now that activation of Akt and MAPK also correlates with sensory neurite elongation and branching [36]. PI 3-K and Akt may be more important for sensory neurite extension and branching than MAPKdependent signalling, which may, in fact, be inhibitory to sensory neuritic branching [36], although this is controversial [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear now that activation of Akt and MAPK also correlates with sensory neurite elongation and branching [36]. PI 3-K and Akt may be more important for sensory neurite extension and branching than MAPKdependent signalling, which may, in fact, be inhibitory to sensory neuritic branching [36], although this is controversial [37]. Elegant compartmentalised culture studies have demonstrated that IGF-1 (but neither fibroblast growth factor nor endothelial growth factor) potentiates distal neurite growth into side compartments only when IGF-1 is applied to cell bodies [37].…”
Section: Discussionmentioning
confidence: 99%
“…One approach involves exogenous application of growth factors, such as nerve growth factor (NGF) (Jones et al, 2003;Kemp et al, 2007). Another uses knock-out of PTEN; however, the loss of PTEN is oncogenic and a long-term knock-out in particular tissues might lead to neoplasia (Ali et al, 1999).…”
Section: Introductionmentioning
confidence: 99%